A Preliminary Quranic Review of Consciousness - Naufanita, Hana; Nurwahidin, Nurwahidin; Ghozali, Ghozali (UI Scholars Hub, 2023)
Consciousness is a classical discourse among scientists, philosophers, and theologians across time and space. It has become a hard problem from many angles: What it is? How do we approach it? How it is being discussed? What is the objective? Etc. The vast scope of the topic causes consciousness to become an intriguing topic to many disciplines. This paper offers multidisciplinary research to consciousness. This approach enables us to spot the problem, intersection, and division across disciplines. We found that there are convergences and divergences to consciousness as multidisciplinary object of study. First, consciousness is related to the mind, but the location is unclear because of the lack of understanding of human structure. Second, spirituality is closely associated with the study of consciousness but remains secondary in Western hegemonic knowledge production, but it is highly encouraged for mental health practices in Western society. Third, some disagreement in investigating consciousness is on the acknowledgment of soul and the sentiment about religion. The dispute implies to various type of consciousness: consciousness as consciousness, self-consciousness, and God-consciousness. This typology correlates to what extent one’s beliefs. We argue that Islam has the most comprehensive explanation to study consciousness and its cognates.